1991
DOI: 10.1149/1.2085856
|View full text |Cite
|
Sign up to set email alerts
|

On the Factors Determining the Morphology of Wet‐Etched n‐ and p ‐ GaP Single‐Crystal Surfaces

Abstract: Wet etching of [1 Ill-oriented GaP single crystals is performed in aqueous KOH solutions at different anodic potentials for p-type and at different anodic potentials and illumination levels for n-type samples. Furthermore, both n-and p-type crystals are photoetched in KOBr solutions at open-cricuit potential. The influence of the rate-determining step on the etching morphology is shown. The difference in etching selectivity between the ( 111) and ( 111) face is explained by the different orientation of the Ga-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…It appears likely that many factors are involved: surface film formation, varying potential drop across the Helmholtz region caused, for example, by surface state charging, and so on. Even crystallographic orientations appear to be important [59]. These aspects have been discussed by other authors [14, 55,60].…”
Section: Current-potential Behaviormentioning
confidence: 74%
See 1 more Smart Citation
“…It appears likely that many factors are involved: surface film formation, varying potential drop across the Helmholtz region caused, for example, by surface state charging, and so on. Even crystallographic orientations appear to be important [59]. These aspects have been discussed by other authors [14, 55,60].…”
Section: Current-potential Behaviormentioning
confidence: 74%
“…( 17) predicts a Tafel slope of 60 mV per decade at 298 K. In many instances [53,54], such a slope indeed is observed. In many cases, however, the slopes are higher than the ''ideal'' value [14, [55][56][57][58][59].…”
Section: Current-potential Behaviormentioning
confidence: 99%
“…Etching of III-V semiconductors is often observed to be anisotropic. For example both chemical [29][30][31][32] and electrochemical 33,34 etching of III-V semiconductors show preferential etching of {111}B planes (i.e. group-V-terminated planes).…”
Section: Introductionmentioning
confidence: 99%
“…The slowest-etching plane is usually {111}A and so these facets are revealed during etching of InP, 35,36 GaAs 34,37,38 and GaP. 31 Due to the differing etch rates of crystal planes, the formation of tetrahedral etch pits (seen as dove-tailed and v-groove voids, respectively, in (011) and (01% 1) cross sections) is observed on the (100) surface of III-V semiconductors. 32,36,37 We have previously investigated [39][40][41][42][43][44] the early stages of pore formation in InP in aqueous KOH electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In a case of GaP, Kaminska et al 1) pointed out that its (111) surface inevitably becomes rough or cloudy during chemical polishing in almost all the etchants. On the other hand, Goossens and Gomes 2) found that anodic dissolution at 1.6 V SCE (potential vs. saturated calomel electrode) in an aqueous 0.1 kmolÁm À3 KOH solution brought about a smooth (111) surface of p-type GaP; although no active dissolution occurred in the (111) surface of n-type GaP at the same etching condition, the anodic photoetching under full light illumination (800 Wm À2 , Hg-lamp) at 1.6 V SCE in the above solution also gave rise to the flat (111) surface. According to them, such an overall etch process proceeds via the photoelectrochemical reaction expressed by the following equation:…”
Section: Introductionmentioning
confidence: 99%